PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN HASIL BELAJAR TEMA 4 (GLOBALISASI) PADA PESERTA DIDIK SDN 4 JATILAWANG - Yuni Indriyani; Ahmad Dwi Agung Prabowo; Tati Heriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The background of this research is the low student learning outcomes, especially in Theme 4, as seen from the results of the students' KKM. The purpose of this research is to improve student learning outcomes through the project based learning model in the learning of Theme 4 Class VI Semester 1 SDN 4 Jatilawang. The subjects of this study were sixth grade students at SDN 4 Jatilawang. This research is a Classroom Action Research which lasts for two cycles consisting of planning, action, observation and reflection stages. Based on the research results obtained in this study, it can be concluded that the learning outcomes of Theme 4 students of class VI SDN 4 Jatilawang can be increased by using the Project Based Learning model. The increase in learning outcomes can be seen from the initial condition of the average score of 64.1 with the percentage of the number of students who completed 42%. In the first cycle there was an increase in the average score of 72.3 with the percentage of the number of students who completed was 67%, with a target of 85%. The second cycle there was an increase in the average score of 83 with the percentage of students who completed 100%, with a target of. Based on the results of the study, it can be concluded that there is an increase in student learning outcomes in Theme 4 using the Project Based Learning model.